Dampak Penerapan Good Governance, Kompetensi SDM, Penerapan SAP, Penerapan SPIP dan Pemanfaatan SIPKD Terhadap Akuntabilitas Publik Dan Kualitas Laporan Keuangan (Pemerintah Kota Jambi) - Etik Winarni; Endah Tri Kurniasih; Ahmad Soleh (Universitas Batanghari, 2020)
The main content in quality development is the implementation of good governance. A reflection of good government implementation can be measured from the level of Public Accountability and Its Financial Statements, because both are indicators to see if a region has run good governance or not. In its context as an organization engaged in public service services, the government in its management must conduct transparency and public accountability. Public accountability in accordance with the characteristics of good governance with respect to (1) participation; (2) rule of low; (3) transparency; (4) responsiveness; (5) consensus orietation; (6) equity; (7) effectiveness and efficiency; and (8) strategy vision (Mardiasmo, 2006). This research aims to analyze the impact of good governance, Human Resources Competency (HR), Implementation of Government Accounting Standards (GAS), Implementation of Government Internal Control System (GICS) and Utilization of Regional Financial Management Information System (FMIS) on Public Accountability and Quality of Financial Report. The study used primary data and secondary data. Primary data is obtained from questionnaires distributed directly to respondents using Purposive Sampling techniques. The population in this study was the Regional Device Task Force (RDTF)/Regional Device Organization (RDO) in jambi city government, with 37 RDTF/RDO and 70 respondents. While the analysis tools used in the study are approaching the Partial Least Squares (PLS) method by negating the assumptions of OLS (Ordinary Least Squares) regression. The results showed that the implementation of good governance, Human Resources Competency (HRC), Application of Government Accounting Standards (GAS) had a positive effect on the quality of Jambi city government financial report. While the implementation of the Government Internal Control System (GICS) and the Utilization of Regional Financial Management Information System (RFMIS) partially did not have a positive effect on the quality of jambi city government financial report. Furthermore, the implementation of good governance, the Implementation of Government Accounting Standards (GAS), the Implementation of Government Internal Control System (GICS) have a positive and significant effect on Public Accountability. While the utilization of regional financial management information system (RFMIS) has not had a positive effect on public accountability.